UJI AKTIVITAS PENURUN KOLESTEROL TOTAL EKSTRAK ETANOL DAUN MURBEI (Morus alba L.) TERHADAP TIKUS PUTIH BETINA(Rattus norvegicus) TAHUN 2014 - NI NYOMAN YULIANI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Mulberry plant is one of the Indonesian plant is often used as a traditional medicine society. Mulberry leaves contain several active ingredients that could be expected to lower the total cholesterol in the blood. Examination using total cholesterol, in addition to significantly cheaper and more frequent, also reflects the overall levels of blood cholesterol. Assuming if total cholesterol levels increased from the normal limit, then it is headed in a state of hypercholesterolemia that must be addressed before it becomes more severe disease. Therefore conducted a study to determine total cholesterol-lowering activity of ethanol extract of mulberry leaves using test animals female white rats (Hundred norvegicus) were 2-3 months old, weighing 100-200 grams. The method used to attract the active substance β-sitosterol from mulberry leaves are percolation method. Female white rats measured total cholesterol levels by using a glucometer (Gluko-Dr) at the time before and after the test solution of ethanol extract of mulberry leaves with each dose of 50 mg, 100 mg, and 200 mg. As for the positive control used for the suspension of simvastatin and negative controls used Na-CMC 0.5%. Observations were carried out for 10 days and is divided into six treatment groups with each group 3 times replication. The data obtained were statistically analyzed using one way ANOVA test (one way ANOVA). These results indicate that the ethanol extract of leaves of mulberry (Morus alba L.) with a dose of 100 mg can lower total cholesterol levels of 8.33 mg / dL and 200 mg can lower total cholesterol by 14 mg / dL in female white mice. It can be concluded that the ethanol extract of mulberry leaves have the effect of lowering total cholesterol levels of the female white rats.